A COMPREHENSIVE MODEL FOR SOFTWARE QUALITY ASSESSMENT IN INFORMATION AND COMMUNICATION SYSTEMS CONSIDERING DYNAMIC PARAMETERS - Gnatyuk, Viktor; Hamretskyi , Roman (Science-based technologies, 2026)
The paper addresses the problem of comprehensive assessment of software quality in information and communication systems (ICS) that operate under dynamic workloads and distributed architectures. The relevance is determined by the limitations of traditional approaches, notably ISO/IEC 25010:2023, which focus mainly on static characteristics and fail to reflect real runtime behavior. This results in a gap between declared quality and actual operational indicators such as latency, throughput, packet loss, and stability, which is particularly critical for 5G/6G networks, SDN/NFV infrastructures, and IoT platforms. The aim of the study is to develop an assessment model that integrates static and dynamic metrics into a single framework and provides an integral quality indicator. The proposed multi-level approach includes: a baseline level covering static metrics from the standard; a dynamic level monitoring latency, throughput, packet loss, and resilience; and an aggregated level producing an integral index with adaptive weighting depending on operational conditions. Validation was carried out in a Proxmox VE virtualization testbed with three representative ICS components: an SDN controller (OpenDaylight), an authentication microservice (Spring Boot), and an IoT telemetry collector (Node.js/MQTT). Network load was emulated with NetEm, while Prometheus and Grafana were used for data collection and visualization. Results indicate that as load increases, dynamic quality metrics degrade by 25–35%. The IoT component was the most sensitive to performance decline, the SDN controller maintained high throughput but lost stability under critical load, and the authentication service exhibited balanced behavior. The findings confirm the necessity of combining static and dynamic characteristics in a unified model and demonstrate its practical applicability. The approach can be integrated into CI/CD pipelines and observability systems for early detection of degradation, reduction of SLA violation risks, and support of deployment, scaling, and update decisions in modern ICS.